Analisis Kebijakan Keselamatan Dan Kesehatan Kerja (K3) Dan Perencanaan Terhadap Kejadian Kecelakaan Kerja - Leli Sundari; Khairul Mufti Rambe; Pangeran Pangeran; Hastuti Olivia (Universitas Muhammadiyah Sumatera Utara, 2022)
Occupational health safety policies in the workplace are motivated by several factors, namely work accidents that have occurred so far are mostly caused by human factors, in addition to technical/environmental factors, the demand for quality products is associated with technical barriers in the era of globalization of trade, preventing social problems arising from from the lack of application of K3 in the workplace, complying with statutory regulations. In this study, the data used were primary data, namely data obtained directly from interviews with PTPN IV Sawit Langkat Unit in Bandar Jaya Village, Padang Tualang District, Langkat Regency related to the research material, as well as secondary data, namely data obtained by researchers with the existence of intermediary, in the form of evidence, records, or historical reports, both published and unpublished. Sources of data were processed and obtained directly from PTPN IV Langkat Sawit Unit in Bandar Jaya Village, Padang Tualang District, Langkat Regency. The results of the study indicate that (1) The conditions for implementing Occupational Health and Safety (K3) policies and planning for the occurrence of work accidents at PTPN IV Sawit Langkat Unit have been carried out well with several policies in accordance with the regulations set by the company in the articles on Safety. and Occupational Health (K3) of its employees such as providing social security, providing good work equipment and carrying out activities in accordance with applicable regulations. (2) Obstacles in the Implementation of Occupational Safety and Health (K3) Policies and Planning for Work Accident Events at PTPN IV Sawit Langkat Unit in Banjar Jaya Village, Padang Tualang District, Langkat Regency, among others, are the lack of awareness of employees to participate in the BPJS Employment program, lack of committee support - the safety committee formed by the company in reducing the risk of work accidents, there is still a lack of understanding of employees in using work safety facilities in addition to the lack of activeness of employees in following directions related to occupational safety and health programs, there is still a lack of awareness of employees in complying with the provisions set by the company so that there are still employees who do not use safety equipment at work. (3) Efforts made in overcoming obstacles to the implementation of Occupational Safety and Health (K3) policies, PTPN IV Sawit Langkat Unit in Bandar Jaya Village, Padang Tualang District, Langkat Regency is to increase employee awareness to take part in the BPJS employment program, ask for the support of the committees safety measures established by the company in reducing the risk of work accidents, increasing supervision of activities carried out by employees on a regular basis, trying to instill safe habits and ways of working for all employees..